ANALYSIS OF VALUATION AND STOCK RETURNS AS A BASIS FOR MAKING STOCK INVESTMENT DECISIONS WITH THE DISCOUNTED CASHFLOW (DCF) METHOD - Zahra, Ghinayatul; Yudhawati, Diah; Maulida, Denia (Universitas Ibn Khaldun Bogor, 2023)
This research is motivated by the development of infrastructure that runs rapidly and results in competition between companies. Therefore the company must be able to survive and improve its business performance to attract more investors to invest. The purpose of this study was to determine the analysis of stock valuation and stock returns in a company as the basis for making stock investment decisions whether undervalued or overvalued by using one of the stock valuation analyzes, namely the Discounted Cash Flow (DCF) method. from the Sea Transportation SubSector Companies Listed on the IDX for the 2017-2021 Period. The results of the analysis in this research are that the condition of the shares of LEAD and MBSS in 2017-2021 is undervalued where the market price is lower than the fair price, so investors should buy these shares. Meanwhile, BBRM, BLTA and HITS 2018 and BBRM, HITS and PTIS in 2020 are overvalued where the market price is higher than the fair price, so investors should sell the company's shares.